The Role of Cystathionine-γ-Lyase In Blunt Chest Trauma in Cigarette Smoke Exposed Mice. Issue 4 (April 2017) - Hartmann, Clair; Hafner, Sebastian; Scheuerle, Angelika; Möller, Peter; Huber-Lang, Markus; Jung, Birgit; Nußbaum, Benedikt; McCook, Oscar; Gröger, Michael; Wagner, Florian; Weber, Sandra; Stahl, Bettina; et al.
Abstract : ABSTRACT: Pretraumatic cigarette smoke (CS) exposure aggravates posttraumatic acute lung injury (ALI). Cystathionine-γ-lyase (CSE) protects against ALI and CS exposure-induced chronic obstructive lung disease (COPD). Therefore, we tested the hypothesis whether genetic CSE knockout (CSE −/− ) would aggravate posttraumatic ALI after CS exposure. After 3 to 4 weeks of CS exposure, anesthetized wild-type (WT) and CSE −/− mice underwent blunt chest trauma, surgical instrumentation and 4 h of lung-protective mechanical ventilation. We measured hemodynamics, lung mechanics, gas exchange, metabolism, and acid–base status together with blood and tissue cytokine and chemokine levels, tissue expression of mediator proteins, parameters of oxidative and nitrosative stress, and histology. CSE −/− mice without CS exposure showed higher cytokine and chemokine levels, and this was further enhanced by CS exposure, particularly in males. CS exposure in WT mice aggravated posttraumatic alveolar membrane thickening, dystelectasis, and inflammatory cell accumulation, which was associated with higher thoracopulmonary compliance. Pretraumatic CS exposure in CSE −/− mice produced a similar response, except for less alveolar membrane thickening, most likely due to lung hyperinflation. CS-exposed WT mice showed the most pronounced metabolic acidosis, while CS exposure in CSE −/− mice resulted in the lowest blood glucose levels. Urinary output and anesthesia rate were highest in male CS-exposed CSE −/− animals. In conclusion, in murine acute-on-chronic pulmonary disease, CSE knockout aggravated posttraumatic inflammation, which was further worsened upon pretraumatic CS exposure, and this effect was particularly pronounced in males. Hence, maintaining CSE expression is critically important for stress adaptation during ALI and CS-induced COPD, most likely in a gender-dependent manner. Abstract : Supplemental Digital Content is available in the text